Bibliometric Study on Sports Nutritional Supplements - Cheng, Guangxin; Yang, Hechong (Journal of Education, Health and Sport, 2025)
Background: This study's objectives are to evaluate and report the current state of publications, authors, journals, nations, institutions, and keywords; investigate popular subjects and opportunities in the area; and suggest future directions for sports nutrition supplement research. Methods: The relevant literature on sports nutrition supplements published globally between 1988 and 2024 was retrieved for this paper using bibliometric techniques and CiteSpace visualization and analysis software. Results: This analysis comprised 527 papers in total, with the most published 133 coming from the United States. The most published institution was MDPI 91, and the most published authors were Stear, S J 49, Burke, L M 48, Castell, L M 47, Chen G P, and Tuan R S. After clustering, the majority of the high frequency keywords from each of the 25 papers were analyzed in parallel. Protein needs, ergogenic aids, endurance, and exercise emerged as the main research topics. Conclusion: 1)An overall fluctuating upward trend was observed in the number of articles published in the study of sports nutrition supplements from 1988 to 2024, according to the number of articles published in the field. 2) The United States, Australia, and the United Kingdom have the largest concentration of research capacity, and there is a greater frequency of reciprocal research collaboration between the United States and nations like Australia, the United Kingdom, Brazil, Spain, etc. Burke, L. M., Castell, L. M., Stear, S. J.,etc. 3) As far as research hotspots go, researchers have recently concentrated on "supplements," "prevalence," "recovery," "sodium," and "sodium bicarbonate." "sports performance," "ioc consensus statement," "recovery," "sodium bicarbonate," "sports supplements," etc. Further research on the in-depth examination and use of functional sports nutrition supplements, the connection between intestinal health and sports nutrition supplements, the safety of sports nutrition supplements, and preventive medicine is anticipated in the future.